Nature in German history - Mauch, Christof (Studies in German history ;, 2004)
"The essays collected in this volume - the first collection on the subject in either English or German - place discussions of nature and the human relationship with nature in their political contexts. Taken together, they trace the gradual shift from a confident belief in humanity's ability to tame and manipulate the natural realm to the Umweltbewusstsein driving the contemporary conservation movement. Nature in German History also documents efforts to reshape the natural realm in keeping with ideological beliefs - such as the Romantic exultation of 'the wild' and the Nazis' attempts to eliminate 'foreign' flora and fauna - as well as the ways in which political issues have repeatedly been transformed into discussions of the environment in Germany."--Jacket